Neoadjuvant Radiation Therapy with Interdigitated High-Dose LRT for Voluminous High-Grade Soft-Tissue Sarcoma - Hatoum GF; Temple HT; Garcia SA; Zheng Y; Kfoury F; Kinley J; Wu X (Cancer Management and Research, 2023)
Georges F Hatoum,1,* H Thomas Temple,2,* Silvio A Garcia,1 Yi Zheng,1,3 Fouad Kfoury,4 Jill Kinley,5 Xiaodong Wu1,3 1Department of Radiation Oncology, HCA Florida JFK Medical Center Comprehensive Cancer Institute, Lake Worth, FL, USA; 2Department of Orthopedic Surgery, University of Miami Miller School of Medicine, Miami, FL, USA; 3Department of Research and Development, Executive Medical Physics Associates, North Miami Beach, FL, USA; 4Pharmacy Department, South Miami Hospital, South Miami, FL, USA; 5Department of Clinical Research, HCA Florida JFK Medical Center, Atlantis, FL, USA*These authors contributed equally to this workCorrespondence: Xiaodong Wu, Executive Medical Physics Associates, 19470 NE 22nd Road, North Miami Beach, FL, 33179, USA, Tel +1 305 775 0333, Email drxiaodongwu@yahoo.comPurpose: To report a case of large extremity soft tissue sarcoma (2933 cc), safely treated with a novel approach of interdigitating high-dose LATTICE radiation therapy (LRT) with standard radiation therapy as a neoadjuvant treatment to surgery.Patients and Methods: Four sessions of high-dose LRT were delivered in a weekly interval, interdigitated with standard radiation therapy. The LRT plan consisted of 15 high-dose vertices receiving a dose > 12 Gy per session, with 2– 3 Gy to the peripheral margin of the tumor. The patient underwent surgical excision 2 months after the new regimen of induction radiation therapy.Results and Discussion: The patient tolerated the radiation therapy regimen well. The post-operative assessment revealed a negative surgical margin and over 95% necrosis of the total tumor volume. The post-surgical wound complication was mitigated by outpatient wound care. Interdigitating multiple sessions of high-dose LATTICE radiation treatments with standard neoadjuvant radiation therapy as a neoadjuvant therapy for soft tissue sarcoma was feasible and did not incur additional toxicity in this clinical case. A phase-I/II trial will be conducted to further evaluate the toxicity and efficacy of the new treatment strategy with the intent to increase the rate of pathologic necrosis, which has been shown to positively correlate with the overall survival.Keywords: sarcoma, SFRT, LATTICE radiotherapy, LRT, chemotherapy, surgery, necrosis